Analysis of coaches’ objectives in artistic gymnastics - Nunomura, Myrian (2017)
The present study is a piece of the main project entitled “Diagnosis of the Artistic Gymnastics Developing Program in Brazil”. Among many issues included in the main study, we analyzed and discussed the coach’s objectives who are coaching incoming gymnasts who are potential to be representative at the national teams. We interviewed 46 coaches from 29 sports institutions in Brazil. As data collection we used a semi-structured interview, and as data treatment we used the content analysis proposed by Bardin (2004). We could evidence that many coaches’ objectives is focused on the competition and the highest level, and that the institutions` emphasis on the results in all levels of categories.